2009
DOI: 10.1002/marc.200800702
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polar Ethylene–Norbornene Copolymers by Metallocene Terpolymerization with Triisobutylaluminium‐Protected But‐3‐en‐1‐ol

Abstract: But-3-en-1-ol has been pre-protected by triisobutylaluminium and terpolymerized with ethylene and norbornene by rac-[Et(Ind)(2) ]ZrCl(2) /MAO catalysts. The strong polarity of diisobutyl(but-3-en-1-oxy)aluminum causes a slight reduction in the catalyst activity and yields a small fraction of crystallinity. The but-3-en-1-ol content in the terpolymer is as high as 3.2% and can be readily adjusted by varying the reaction conditions. When the norbornene/ethylene ratio is over 10, the norbornene incorporation effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The preparation of the E‐NB copolymer and E‐NB‐P terpolymer samples used in this work had been reported in literature 21–24. The composition, molecular weight, and PDI data were cited from the sources.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of the E‐NB copolymer and E‐NB‐P terpolymer samples used in this work had been reported in literature 21–24. The composition, molecular weight, and PDI data were cited from the sources.…”
Section: Methodsmentioning
confidence: 99%
“…In 1989, Kaminsky developed a process of synthesis using metallocene catalysts, in particular zirconocene and half-sandwich titanium methylaluminoxane (MAO) catalysts [47][48][49][50], allowing the development of a perfectly transparent material with a great rigidity, which was in the centre of several research efforts [35,[51][52][53][54][55][56][57][58][59][60]. Among the commercial COC, norbornene (or Bicyclo[2.2.1]hept-2-ene), 1, 3-dicyclopentadiene and 5-vinyl-2-norbornene can be found as cyclic olefins.…”
Section: Cyclic Olefin Copolymers (Coc) Development Of Cyclic Olefin mentioning
confidence: 99%
“…The opportunity of incorporating other olefins (as a third monomer) into the poly(ethylene-co-norbornene) backbone may lead to improvements in the mechanical or other physical properties of the polymer. There are only a few reports on terpolymerization of ethylene and norbornene [28][29][30][31]. The introduction of a termonomer, either a linear α-olefin, such as 1-octene (O), or an alicyclic α-olefin, like vinylcyclohexane, has been reported by Marconi et al [29], but a strong decrease of Mw has been observed for both 1-octene and vinylcyclohexane.…”
Section: The Norbornene (N) Content In the Mainmentioning
confidence: 99%
“…The resonances of all of these structural units, reported in Table 3, were attributed on the basis of a comparison with those reported in the literature [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Scheme 1 describes the possible paths leading to terpolymer chain unsaturation with a last-inserted E, N, O or Nx (C5N or C8N) unit.…”
Section: (A) Poly(eter-n-ter-c5n); (B) Poly(e-ter-n-ter-c8n); and (C)mentioning
confidence: 99%